Investigation of the Effect of a New Type of Copper–Sucrose Complex Compound on the Yield and Quality Parameters of Winter Wheat (Triticum aestivum L.) - Renátó Kalocsai; Zsolt Giczi; Dávid Vasas; Judit Molnár; Pál Szakál; Zoltán Varga; Eduárd Gubó; Pál Szakál; Viktória Margit Vona; Erika Krániczné Mayer; Balázs Ásványi; Tamás Szakál (Agronomy)
We conducted experiments on winter wheat grown in copper-deficient soil, where soil tests revealed a more pronounced deficiency in the deeper layers. As climate change reduces precipitation, plants increasingly rely on nutrients from these deeper layers. A copper–sucrose complex—previously unused in agriculture—was applied as a foliar spray during the tillering and flowering stages. Across the three-year average, significant increases were observed starting from the 1 kg ha−1 copper dose in yield, from 0.3 kg ha−1 in crude protein content, and from 0.5 kg ha−1 in wet gluten content compared to the untreated control. For all three parameters, the highest values were achieved with the 2 kg ha−1 dose. Yield increased by 1.03 t ha−1, crude protein by 0.9%, and wet gluten by 2.3% relative to the control. In 2019, high humidity and favorable temperatures during flowering led to fungal infections in control plots, with DON toxin concentrations exceeding the regulatory safety threshold. Following copper–sucrose complex application, DON levels dropped below this threshold, demonstrating a measurable protective effect.